Evaluating the role of nursing interventions in enhanced recovery after surgery for minimally invasive spine surgery: a retrospective analysis - Zhang, Dan; Ding, Hongmei; Shen, Caiping; Liu, Yanyan; Jia, Nan (Frontiers in Surgery, 2025)
BackgroundEnhanced Recovery After Surgery (ERAS) protocols have revolutionized postoperative care, particularly in minimally invasive spine surgery (MISS). This study aims to evaluate the role of nursing interventions in improving patient outcomes and reducing healthcare costs within this framework.MethodsThis retrospective cohort study evaluated 150 patients undergoing MISS at The First Affiliated Hospital of Guangzhou University of Chinese Medicine from January 2017 to December 2021. Of these, 75 were assigned to the conventional group and 75 to the ERAS group. The study compared conventional nursing care with the ERAS protocol, assessing clinical outcomes and hospital expenses.ResultsThe analysis revealed that implementing targeted nursing interventions significantly decreased the length of hospital stay (LOS) in the ERAS group compared to the conventional group (3.2 days vs. 4 days; p < 0.001). Moreover, the multivariate analysis demonstrated that the patients in the the conventional group had significantly higher odds of prolonged length of stay (LOS) as compared to the ERAS group (OR: 5.114; 95% CI: 2.345–11.152, p < 0.001). Furthermore, postoperative drainage volumes were markedly lower in the ERAS group than in the conventional cohort (p < 0.001). Opioid consumption was also reduced, with only 24% of patients in the ERAS group requiring opioids, compared to 45.3% in the conventional care group (p = 0.01). Additionally, the ERAS protocol resulted in lower overall hospital expenses, highlighting its cost-effectiveness in enhancing patient outcomes.ConclusionThe implementation of targeted nursing interventions within the ERAS protocol significantly improves patient outcomes in MISS. The ERAS group demonstrated shorter hospital stays, reduced postoperative drainage, and lower opioid requirements compared to the conventional care group. Additionally, the cost-effectiveness of the ERAS protocol highlights its potential to enhance overall healthcare efficiency.